Modulation of the Optical Properties of Monolayer WS2 by the Single-Atom Sites - Li, Songze (Langmuir : the ACS journal of surfaces and colloids, 2025)
Monolayer tungsten disulfide (ML WS2) exhibits remarkable optical and electrical properties, but its limited light absorption hinders its application in next-generation sensors and optical detectors. Therefore, it is vital to design mixed-dimensional heterostructure (MDH) interfaces that enhance overall absorption and facilitate the effective transfer of photogenerated carriers simultaneously. In this study, MDHs consisting of zero-dimensional (0D) single-site single-tungsten-atom oxides (STAOs) and two-dimensional (2D) ML WS2 were successfully constructed. The optical properties of ML WS2 have been comprehensively characterized by using a series of optical techniques including absorption, photoluminescence (PL), and Raman techniques. In comparison to the case of ML WS2, both geometric configurations (WS2/STAO/SiO2 and STAO/WS2/SiO2) show similar results in the absorption and PL spectra: the absorption of the heterostructures is enhanced, and meanwhile, STAOs significantly reduce the PL intensity of the A-exciton in ML WS2, while increasing the trion-to-exciton intensity ratio. These results suggest that a charge transfer process may occur between STAO and WS2 due to the formation of heterostructures interactions. In order to confirm the existence of the charge transfer, copper phthalocyanine (CuPc) has been chosen as target molecules in surface-enhanced Raman spectroscopy (SERS) experiments for both geometric configurations. It is interesting to see that Raman signals of CuPc show almost no enhancement and sometimes even the quenching effect in the case of STAO/WS2, while in the case of WS2/STAO, they exhibit an STAOs amount-dependent exponential enhancement trend, with an enhancement factor up to ∼37 at 1531 cm-1 peak. Furthermore, Vienna Ab initio Simulation Package (VASP) theoretical calculations confirm that electrons can efficiently transfer from STAO to WS2, which is consistent with our experimental results. Our work demonstrates a method for tuning the optical properties of 2D materials via single sites, providing new strategies and evidence for employing MDHs in sensitive and multifunctional optoelectronic devices